Colloid Chemical Rheology of Non-Aqueous Advanced Electroceramic Slips - Bambang Ari Wahjudi (Institut Teknologi Bandung, 1997)
In many, if not all ceramic industries it is becoming increasingly important to be able to understand and quantify processing behaviour of materials such that final product performance can be accurately determined. In the present work, the usefullness of the so called Stress-Controlled Rheometer in characterising the rheological properties of alumina slips is demonstrated. The alumina slips investigated exhibit more Newtonian character with predominating viscous component at low frequencies, on the other hand shifted to about 22% viscoelastic character at higher oscillating frequencies. Rheological behaviour reflects the extent of interparticulate interaction in a manner that polymer chains conformation is responsible for either the observed elastic nature or dissipative viscous character of flow. Further, it is also revealed that viscoelasticity in a ceramic slip is determined largely by the extent of polymer barrier interpenetration in the overlapped region.